Influence of Optiglaze Material on Wear Resistance of Thermoplastic Resin (Mustansiria Dental Journal, 2022)
Statement of problem: The wear resistance for flexible denture base material. Purpose: The purpose of the study was to measure the wear resistance, of flexible acrylic denture base material; after being coated with light-polymerized glaze material.Materials and methods: A total of (30) Thermoplastic resin specimens were divided into three groups according to the tests, each group consisted of 10 specimens (A) control group had no surface treatment, group (B) specimens surface was treated with Optiglaze materials after finishing and polishing; group (C) specimens was treated with Optiglaze materials after finishing only without polishing. Each specimen's weight loss was measured by comparing the weights before and after the wear test. Collected data were statistically analyzed using SPSS.Results: The results of this study showed the higher mean values for wear resistance was registered by (C) group which was 8.7420,followed by (B) group which was 7.3210,while the lowest mean value related to the (A) group which was 7.0907. Conclusion: Statistically wear values were lower for groups C & D and higher in group A.Clinical implications: This study may be useful in assisting dental professionals and technicians in selecting the best polishing and coating material for dentures. Coating flexible acrylic resin denture materials with an Optiglaze to improve wear resistance.